Community Knowledge Training on Understanding Investment in the Capital Market with Accessible Capital - Evander Naghatur Jaffe (Community Service Akseprin Journal, 2025)
This service helps close the gap between the possible profits from the capital market and the investment knowledge and involvement of everyday people, who often think that investing requires a lot of money and complicated steps. The primary issue is the inadequate financial inclusion in quantifiable risk investment vehicles, such as equities and mutual funds. This initiative aims to enhance financial literacy and promote public engagement by presenting investment concepts on the capital market with accessible capital. This service's innovation is in the Financial Inclusion for Millennials (FIM) Module, which emphasizes practical simulation of establishing a digital Customer Fund Account and executing initial transactions with mutual fund instruments and fractional shares. The findings indicated a 40% rise in the average investment literacy score among participants, with 75% successfully executing their first investment transaction, hence facilitating genuine access to the capital market